The Relationship Between Pregnant Women Hair Loss And Ferritin Levels And Vitamin D3 In Salah Al-Din Governorate - Hussam Dawood Abdullah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The purpose of the current study was to look into the connection between hair loss in thefirst and second trimesters of pregnancy and the levels of vitamin D3 and ferritin in bloodserum of pregnant at Tikrit Hospital. The participants in the study varied in age from 22to 38 years old, and the sample consisted of 50 pregnant women experiencing hair loss inthe first and second trimesters of their pregnancy. A comparison group consisted of 30pregnant women who did not experience hair loss. Every research participant had theirserum levels of ferritin, vitamin D3, white blood cell counts, and platelet counts tested.When compared to women who did not experience hair loss during the first and secondtrimesters of pregnancy, Vitamin D3& ferritin levels were found to be significantlyreduced in women who experienced hair loss throughout the first and second trimestersof pregnancy, compared to normal levels in woman who did not associated with hair lossbut rather their variations were explained by the typical physiology of pregnancy .